(untitled) (Community Based Medical Journal, 2021)
Solid pseudopapillary neoplasm (SPN) of the pancreas, also referred to as Frantz’s tumour, is a rare tumour and represents 1-3% of all pancreatic tumours, which typically affects young women without significant clinical symptoms. This cross-sectional study was done in the Department of Pathology, Bangabandhu Sheikh Mujib Medical Un iversity (BSMMU) between January 2009 and December 2015. A total of nineteen cases of solid pseudopapillary neoplasm (SPN) of pancreas were detected in patients and included in this study. In all the patients the diagnosis was confirmed by histopathology after the surgery. Tumours were nodular, cystic or solid-cystic, often encapsulated. Some of them were received as irregular fragmented pieces, as intact removal was not possible. Cut surfaces were partly grey-white and partly tan-brown with cystic degeneration. Areas of necrosis and hemorrhage were present in all the specimens.The age range was of 14-45 years (mean age 26.9±3.7 years) (Table-I). Among the tumours, 18 were found in female patients, while only 1 was from male patient. In all the cases, preoperative imaging contributed to diagnosis of an abdominal mass in the patients. 11 of these were reported as pancreatic mass, while 3 as pancreatic cystic mass, 2 as retroperitoneal mass, 2 as mesenteric mass and only 1 as adrenal mass. Tumour-size ranged from 6 to 19 cm (mean size 9.3±1.5 cm). 7 tumours were solid and cystic in nature, while 8 were solid and 4 were only cystic. Complete capsule was found in 17 specimens. Calcifications were found in only 5 specimens. Surgical resection was found generally curative. In our study, absence of metastasis suggests that these tumours hardly show aggressive clinical behaviour. However, follow-up is important to observe potential local recurrence and metastasis. CBMJ 2020 July: Vol. 09 No. 02 P: 34-38